Peningkatan Kemampuan Berpikir Kritis Materi Pembagian Kelas III Melalui Pendekatan Kontekstual Pada Media Canva - Solikah, Arum; Fahira, Nindi Itsna; Qotrunnada, Shofiya; Faiziyah, Nuqthy; Muchsin, Ernawati (WASIS : Jurnal Ilmiah Pendidikan, 2025)
The aim of this research is to improve Critical Thinking Ability and Learning Outcomes through the application of the Contextual Teaching Learning (CTL) model assisted by Canva media. The type of research used was Classroom Action Research (PTK) with the research subjects being class III students at SD Muhammadiyah 3 Surakarta, totaling 27 students. Data collection techniques include observation, interviews, tests and non-tests. The data analysis techniques used are quantitative descriptive and qualitative descriptive. The results of this research consist of two cycles: (1) cycle I from the application of the Contextual Teaching Learning (CTL) model, critical thinking skills with an average of 33%, then for learning outcomes the average was 40.7%; (2) cycle II is a follow-up to the weaknesses and deficiencies in the first cycle, at this stage the results of critical thinking skills increase by 70%, then the average learning results are 85%. Based on the research results, it can be concluded that the application of the Contextual Teaching Learning (CTL) model approach can improve critical thinking skills and learning outcomes for class III students at SD Muhammadiyah 3 Surakarta.